2009
DOI: 10.3201/eid1512.090788
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transmission of Bluetongue Virus 8 in Cattle, UK

Abstract: To determine whether transplacental transmission could explain overwintering of bluetongue virus in the United Kingdom, we studied calves born to dams naturally infected during pregnancy in 2007–08. Approximately 33% were infected transplacentally; some had compromised health. In all infected calves, viral load decreased after birth; no evidence of persistent infection was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 11 publications
1
59
0
1
Order By: Relevance
“…The BTV-8 strain from Europe, which is the same as the BTV-8 strain currently circulating in Israel, is currently considered to be unique as a field strain in its ability to cross the placenta and infect unborn calves (Darpel and others 2009). Previously it was thought that only laboratory-adapted strains of BTV, such as the live attenuated vaccine strains, were capable of transplacental transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The BTV-8 strain from Europe, which is the same as the BTV-8 strain currently circulating in Israel, is currently considered to be unique as a field strain in its ability to cross the placenta and infect unborn calves (Darpel and others 2009). Previously it was thought that only laboratory-adapted strains of BTV, such as the live attenuated vaccine strains, were capable of transplacental transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental infection with the current European strain of BTV-8 has been investigated extensively in both sheep and cattle in experimental Backx et al, 2009;van der Sluijs et al, 2011) and field studies (De Clercq et al, 2008;Darpel et al, 2009a;SantmanBerends et al, 2010;Saegerman et al, 2010) in north-western Europe. Field surveys have indicated that the virus was extremely efficient at crossing the placenta.…”
Section: Several Characteristics Of the 2006-2008 Outbreak Of Btv-8 Imentioning
confidence: 99%
“…Persistence in a host may be related to long viremia, to vertical transmission, or to a chronic infection phenomenon with resurgent viremia. For example, in the Culicoides /bluetongue virus system, cattle present a long viremia and the transmission of the virus from a cow to her calf is possible [5], [6]. In the Culex /Western equine encephalitis virus system, a resurgence of viremia was observed experimentally in snakes after hibernation [7].…”
Section: Introductionmentioning
confidence: 99%